A suspicious case of hyponatremia: Pseudomembranous colitis can present with severe hyponatremia even in the absence of diarrhoea (Indian Journal of Case Reports, 2021)
Pseudomembranous colitis commonly manifests with abdominal pain, diarrhea, fever, and leukocytosis. The mortality rate is high (>60%) in patients whose condition is not diagnosed and treated. Here, we report the case of a 65-year-old male with a history of diabetes, hypertension, and asthma who presented to the emergency department with complaints of generalized weakness and dizziness for 3 days. The evaluation revealed leukocytosis and severe hyponatremia. There were no symptoms of diarrhea Or vomiting. Further evaluation of the source of leukocytosis revealed pseudomembranous colitis and was managed appropriately. In this article, we describe an unusual case of hyponatremia secondary to pseudomembranous colitis without associated diarrhea, necessitating a high index of suspicion to avoid the potentially disastrous effects of the disease.